CO2 laser cutting of natural granite. (January 2016) - Riveiro, A.; Mejías, A.; Soto, R.; Quintero, F.; del Val, J.; Boutinguiza, M.; Lusquiños, F.; Pardo, J.; Pou, J.
Abstract: Commercial black granite boards (trade name: "Zimbabwe black granite") 10 mm thick, were successfully cut by a 3.5 kW CO2 laser source. Cutting quality, in terms of kerf width and roughness of the cut wall, was assessed by means of statistically planned experiments. No chemical modification of the material in the cutting walls was detected by the laser beam action. Costs associated to the process were calculated, and the main factors affecting them were identified. Results reported here demonstrate that cutting granite boards could be a new application of CO2 laser cutting machines provided a supersonic nozzle is used. Highlights: Natural granite stone plates have been successfully cut by CO2 laser. Supersonic nozzle to inject the assist gas is required. A minimum roughness Ra=30 µm at a maximum cutting speed of 6 mm/s was obtained. Cut quality was better when cutting in continuous wave mode than in pulsed one.